2022
DOI: 10.3390/ma15041335
|View full text |Cite
|
Sign up to set email alerts
|

Intermetallics Formation during Solidification of Al-Si-Cu-Mg Cast Alloys

Abstract: The present study was undertaken to examine the effect of iron, manganese, copper and magnesium on the microstructural characteristics of Al-11%Si-2%Cu-Mg-based alloy referred to as 396 under different working conditions. The results show that strontium (Sr) has high affinity to react with magnesium (Mg), resulting in reduced effectiveness as eutectic silicon modifier or age hardening agent. In addition, Sr alters the sequence of the precipitation of the α-AlFeMnSi phase from post-eutectic to pro-eutectic whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…In Figure 9 e,f, we also found the second phase containing Cu, Fe, and Mn enrichment. From the literature, we know that this is an impurity phase formed during casting [ 39 , 40 ], the content of Fe and Mn phase is very low and the solid solubility in Al is very low at 495 °C [ 41 , 42 ], so we will not discuss this second phase in this paper.…”
Section: Resultsmentioning
confidence: 99%
“…In Figure 9 e,f, we also found the second phase containing Cu, Fe, and Mn enrichment. From the literature, we know that this is an impurity phase formed during casting [ 39 , 40 ], the content of Fe and Mn phase is very low and the solid solubility in Al is very low at 495 °C [ 41 , 42 ], so we will not discuss this second phase in this paper.…”
Section: Resultsmentioning
confidence: 99%
“…The properties of alloys may be improved by adding Cu, Fe, and Sr to the alloys. Mohamed et al [21,22] reported on the changes in the microstructure (i.e., with respect to intermetallics and silicon particle characteristics) with the addition of Fe, Mn, Cu, Sr, and Mg to Al-10.8%Si near-eutectic alloys. The results showed that increasing the level of Mg and Cu in the Sr-containing alloys produced larger Si particle sizes, thus, in effect, diminishing the modifying influence of Sr.…”
Section: Discussionmentioning
confidence: 99%
“…The impact energy increases considerably from the peak-aged to overaged condition due to precipitation and microstructural coarsening of the alloys. The figure also shows how trace added alloy as a microstructural alteration by Zr addition has a favorable impact on impact energy [19], [20]. It can be said in other words that the addition of Zr obviously reduced the Si particle size and changed its morphology resulting in reduced brittleness.…”
Section: A Interpretation Of Tensile Testsmentioning
confidence: 96%